Representasi Nilai-Nilai Budaya dalam Tari Kejei di Kecamatan Binduriang, Kabupaten Rejang Lebong, Provinsi Bengkulu - Pratiwi (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research aims to understand the role and meaning of Dance Art in the context of local culture, with a focus on the representation of Kejei dance in the Binduriang District of Bengkulu. Using a Semiotic approach in descriptive qualitative research methodology, the analysis of Kejei dance reveals that each element of the dance, such as movements, costumes, and music, holds profound symbolic meaning, showcasing the social, cultural, and aesthetic values of the Binduriang community. The research findings affirm that Kejei dance is not merely entertainment, but also serves as a means of preserving cultural heritage and traditions, as well as a strong cultural identity for the local community, with significant implications for regional cultural development. The representation of Kejei dance also plays a vital role in preserving the cultural heritage and traditions of the Binduriang community. Through this dance, younger generations can learn and respect the culture and traditions passed down by their ancestors for generations. Overall, the representation of Kejei dance in the Binduriang District of Bengkulu embodies the cultural richness and traditions of the local community, and is highly important for the development of regional culture and heritage.Keywords: Representation of Cultural Values, Kejei Dance